UNDERSTANDING FEDERAL INSTITUTIONAL ARCHITECTURE AND DYNAMICS IN BOSNIA AND HERZEGOVINA - Sajic, Nina (Politeia, 2024)
Federalism has come to be seen as an important tool for conflict resolution and management providing a framework suitable to accommodate diversity, equal representation, and democracy. This article analyses the federal institutional architecture and dynamics in Bosnia and Herzegovina. The methodology used in this article is the one of a case study analysis. By applying single case analysis to our study, we will be able to examine the particularities of Bosnia and Herzegovina's federal system, we will look at distribution of competences , inter-governmental relations, and the impact of these structures on governance and internal dynamics. The goal of this article is to contribute to a broader understanding of federalism, especially to its role in post-conflict societies and multi-ethnic countries.
Keywords: federalism; Bosnia and Herzegovina; federal dynamics; post conflict structures